2-Hydroxy-10-propargylpyrrolo[2,1-c][1,4]benzodiazepine-5,11-dione monohydrate - Ourahou, S.; Chammache, M.; Zouihri, H.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The title compound, C(15)H(14)N(2)O(3)center dot H(2)O, consists of a benzodiazepinedione system fused to a pyrrole system. The seven-membered ring adopts a boat-shaped conformation (with the methine C atom as the prow); the five-membered ring adopts an enveloped-shaped conformation (with the hydroxy-bearing C atom as the flap). In the crystal, adjacent molecules are linked by O-H center dot center dot center dot O hydrogen bonds into sheets parallel to (102). In addition, C(acetylinic)-H center dot center dot center dot O hydrogen bonds occur.